Sur Un Balcon en Forêt - Alain Trouvé (Carnets)
This article looks at the mechanisms of literary writing-reading in Julien Gracq's Un balcon en forêt. This novel marks in the author a shift from dream writing to realism, which accentuates its divergence from André Breton's Surrealist Manifesto. It is favored by Gracq's dual profession of historian-geographer and man of letters. Not everything in this writing can be explained by the relationship between texts, in other words by intertextuality. Whether it is the space, the characters, or the "playing" offered to the reader (s), the analysis resorts to the notion of arrière-texte, accorded to the hors-texte as well as the "out-of-language", in order to make its particular accents heard.